The Effect of Perinatal Hypoxia on Red Blood Cell Morphology in Newborns - S. A. Perepelitsa; V. A. Sergunova; O. E. Gudkova (Общая реаниматология)
Aim. To study the red blood cell (RBC) morphology in newborn infants with a history of perinatal hypoxia using the atomic-force microscopy. Material and methods. The state of RBC membranes of 10 newborns with a history of perinatal hypoxia was studied. All infants were born with low Apgar scoring; the following resuscitative measures were carried out at birth: tracheal intubation, mechanical ventilation (MV). The study group newborns were transferred from the delivery room to the ICU, where MV was started. To obtain images of normal red blood cells in the field of the atomic force microscope (AFM), 14 full-term newborns delivered after a favorable course of pregnancy and normal term labor were enrolled in a reference group. Results. Discocytes and planocytes comprised 36% of the total red blood cell count in the residual umbilical cord blood of newborns with a history of perinatal hypoxia; there was a decreased amount of normal RBC forms, thus demonstrating an unfavorable effect of hypoxia on newborn's RBC membrane. Poikilocytosis was typical for infants exposed to perinatal hypoxia; transitional forms of RBCs (stomatocytes and echynocytes) were visualized. Stomatocytosis and echynocytosis were typical for 80% of newborns. Stomatocytosis persisted in full-term newborns exposed to hypoxia complicated with aspiration of neonatal meconium. The analysis of RBC membrane nanostructure demonstrated that the first-order height (h1) experienced the greatest alterations at birth in newborns with perinatal hypoxia; it was 4.2 times as much as the similar parameter in healthy newborns. Estimations of second-order height (h2) parameter values demonstrated a two-fold increase showing that the spectrin matrix also changed under the effect of hypoxia. The third order value (h3) was significantly higher in newborns with perinatal hypoxia, than that in healthy infants. Therefore, perinatal hypoxia causes antenatal complete damage of nanostructures of RBC membranes. Conclusion. Perinatal hypoxia alters RBC morphology and impairs the nanostructure of membranes. These changes confirmed the effect of the hypoxia degree on all nanostructures of RBC membranes: phospholipid bilayer, protein elements of the membrane, spectrin matrix. Changes in heights and spatial periods of the red blood cell membrane surfaces h1 and h3 associated with hypoxia apparently are aimed at a compensatory increase in the red blood cell membrane surface contributing to the increase of the gas exchange area. These changes may represent adaptive responses to hypoxia aimed to preserve the functional capabilities of red blood cells. The course of an early adaptation period (post-hypoxic period) is characterized by the instability of all nanostructures of red blood cell membranes and a greater variability of morphological forms. Effects of perinatal hypoxia on the red blood cell membrane persist for some time and go beyond the early neonatal period.